On house calls, healthcare, and hope: one student's perspective - Ryan Shelquist; Elisa Greene (University of Minnesota Libraries Publishing, 2014)
Healthcare providers spend years studying pathophysiology and therapeutics, often neglecting to consider the whole picture of influences on a person's health. House calls are a beneficial tool in that they provide the opportunity for trainees to experience these concepts firsthand, often opening student eyes to suffering, poverty, and unexpectedly, hope. Exposure to this broader perspective may empower health care providers to see beyond the limitations of disease and medication, into deeper issues that affect patient health.   Type: Idea Paper